Best Environmental Practices in Metal Ore Mining - Kauppila, Päivi; Räsänen, Marja Liisa; Myllyoja, Sari (Finnish Environment Institute, 2013)
Over the past few years, important new mines have been opened in Finland (Suurikuusikko, Talvivaara) while existing ones have upscaled their operations and new mining projects have been started. The mining industry produces the raw materials on which many other industries depend, including the metal, chemical and pulp and paper industries, as well as agriculture and a number of other sectors. Unavoidably, the metal ore mining has impacts on the environment. Prevention of negative environmental impacts calls for the application of BAT (Best Available Techniques) in the mining, starting from ore prospecting and mine planning and extending to mine closure - throughout the mine life cycle. This publication discusses the environmental aspects of metal ore mines throughout the mine life cycle, ranging from the relevant legislation, emissions and environmental impacts of the mining, to the required environmental surveys, methods and techniques used to decrease emissions and diminish environmental impacts. With Finnish conditions in focus, the publication proposes latest solution models for the best environmental practices for the metal ore mining. The publication is a joint project between the Geological Survey of Finland, the Kainuu and Lapland Centres for Economic Development, Transport and the Environment, the Regional State Administrative Agency for Northern Finland, the Finnish Association of Extractive Resources Industry and the Finnish Environment Institute. The publication is intended to use in planning, implementing and closing of the mines for operators and permit and supervisory authorities, as well as for consultants.